Unravelling the Origin of Ultra‐Low Conductivity in SrTiO3 Thin Films: Sr Vacancies and Ti on A‐Sites Cause Fermi Level Pinning. (7th July 2022) - Morgenbesser, Maximilian; Viernstein, Alexander; Schmid, Alexander; Herzig, Christopher; Kubicek, Markus; Taibl, Stefanie; Bimashofer, Gesara; Stahn, Jochen; Vaz, Carlos Antonio Fernandes; Döbeli, Max; Biautti, Federico; de Dios Sirvent, Juan; et al.
Abstract: Different SrTiO3 thin films are investigated to unravel the nature of ultra‐low conductivities recently found in SrTiO3 films prepared by pulsed laser deposition. Impedance spectroscopy reveals electronically pseudo‐intrinsic conductivities for a broad range of different dopants (Fe, Al, Ni) and partly high dopant concentrations up to several percent. Using inductively‐coupled plasma optical emission spectroscopy and reciprocal space mapping, a severe Sr deficiency is found and positron annihilation lifetime spectroscopy revealed Sr vacancies as predominant point defects. From synchrotron‐based X‐ray standing wave and X‐ray absorption spectroscopy measurements, a change in site occupation is deduced for Fe‐doped SrTiO3 films, accompanied by a change in the dopant type. Based on these experiments, a model is deduced, which explains the almost ubiquitous pseudo‐intrinsic conductivity of these films. Sr deficiency is suggested as key driver by introducing Sr vacancies and causing site changes (FeSr and TiSr ) to accommodate nonstoichiometry. Sr vacancies act as mid‐gap acceptor states, pinning the Fermi level, provided that additional donor states (most probably Ti Sr \[{\rm{Ti}}_{{\rm{Sr}}}^{ \bullet \bullet }\] ) are present. Defect chemical modeling revealed that such a Fermi level pinning also causes a self‐limitation of the Ti site change and leads to a very robust pseudo‐intrinsic situation, irrespective of Sr/Ti ratios and doping. Abstract : To investigate the ubiquitous ultra low conductivities found in various doped and undoped SrTiO3 thin films a wide range of chemical, physical, and electrical analysis techniques is employed. A novel defect chemical model is developed, explaining these ultra low conductivities as a consequence of mid‐gap states introduced by cation vacancies.